Composition dependent microstructure evolution, activation and de-/hydrogenation properties of Mg–Ni–La alloys. (21st June 2019) - Guo, Fenghai; Zhang, Tiebang; Shi, Limin; Song, Lin
Abstract: In this work, in order to elucidate the effect of different alloying elements on the microstructure, activation and the de-/hydrogenation kinetics performance, the Mg–20La, Mg–20Ni and Mg–10Ni–10La (wt.%) alloys have been prepared by near equilibrium solidification combined with high-energy ball milling treatment to realize the internal optimization as well as particle refinement. The results show that the microstructures of the prepared alloys are significantly refined by forming different types and sizes of intermetallic compounds. Meanwhile, the effects of LaH3 and Mg2 Ni within the activated samples on de-/hydrogenation kinetics are also discussed. It is observed that the alloy containing LaH3 preserves stable hydrogenation behavior between 573 and 623 K, while the hydrogenation properties of the alloy containing Mg2 Ni is susceptible to temperature. A preferable hydrogenation performance is observed in Mg–10Ni–10La alloy, which can absorb as high as 5.86 wt% hydrogen within 15 min at 623 K and 3.0 MPa hydrogen pressure. Moreover, the desorption kinetics and the desorption activation energies are evaluated to illustrate the mechanism based on improved dehydrogenation performance. The addition of proper alloying elements Ni and La in combination with reasonable processing is an effective strategy to improve the de-/hydrogenation performance of Mg-based alloys. Highlights: Novel Mg–Ni–La alloys have been obtained by microstructural design. Microstructural related de-/hydrogenation of Mg–Ni–La has been proposed. This work clarifies temperature dependent de-/hydrogenation kinetics of Mg–Ni–La. Rate-limiting steps and desorption activation energies of Mg–Ni–La are illustrated.